User Interface Layanan Mandiri Untuk Gelanggang Olahraga Menggunakan Metode Design Thinking - Muhammad Reinaldy Gunawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Exercise is needed in the community to keep the body healthy and can also maintain immunity.In the field of sports most of the community uses a sports arena to do its activities.The Sports Arena (GOR) itself is a sports facility intended for a variety of sports activities in it.The way to access a GOR is a little difficult because it has to meet with the existing administrators.It was considered less efficient because customers had to search and wait a long time until the caretaker arrived.By reviewing this problem, a solution is needed to create a self-service system.But in the results of this study is designing a user interface for customers ordering their own gor.By using design thinking method the customers will access a gor without having to search or meet with the administrator.